A longitudinal cohort study of the anti-synthetase syndrome: increased severity of interstitial lung disease in black patients and patients with anti-PL7 and anti-PL12 autoantibodies. (4th March 2017) - Pinal-Fernandez, Iago; Casal-Dominguez, Maria; Huapaya, Julio A.; Albayda, Jemima; Paik, Julie J.; Johnson, Cheilonda; Silhan, Leann; Christopher-Stine, Lisa; Mammen, Andrew L.; Danoff, Sonye K.
Abstract: Objective. The aim was to study the prevalence, rate of appearance and severity of clinical features in patients with different anti-synthetase syndrome (ASyS) autoantibodies. Methods. All Johns Hopkins Myositis Longitudinal Cohort subjects positive for any ASyS autoantibodies were included. Clinical information, including symptoms, signs, strength, creatine kinase concentrations and pulmonary function tests, were prospectively collected. The standardized mortality and cancer rates and the rate of appearance and intensity of the different organ manifestations were assessed using univariate and multivariate analysis and compared between ASyS autoantibodies. Results. One hundred and twenty-four (73.4%) patients were positive for anti-Jo1, 23 (13.6%) for anti-PL12, 16 for anti-PL7 (9.5%) and 3 (1.8%) for anti-EJ or anti-OJ, respectively. The mean length of follow-up was 4.1 years. Anti-PL12 was more frequent in black subjects. Anti-PL12 and anti-PL7 were associated with more prevalent and severe lung involvement, often without muscle involvement. Anti-Jo1 displayed more severe muscle involvement compared with anti-PL12 patients. Concurrent anti-Ro52 was more prevalent in anti-Jo1 patients and was associated with earlier development of mechanic's hands, DM-specific skin findings and arthritis. Independent of ASyS antibody status, black patients demonstrated more severe lung involvement than white patients. There was no significant increase in mortality or cancer risk in ASyS patients compared with the general US population. Conclusion. Different ASyS autoantibodies are associated with phenotypically distinct subgroups within the ASyS spectrum. Anti-PL7 and anti-PL12 are characterized by more severe lung involvement, whereas anti-Jo1 is associated with more severe muscle involvement. Black race is a major prognostic factor associated with lung disease severity.